2019
DOI: 10.1111/geer.12162
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence on the Effects of the Shortened School Duration in the German States: An Evaluation of Post-secondary Education Decisions

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Another explanation for the gender heterogeneity (and especially the opposite-signed effects in STEM occupations) could be different responses to changes in competitive pressure. As studies on double high school graduation cohorts show, greater competition increases the performance of males relative to females (Ors et al, 2013;Morin, 2015), while the educational attainment of females tends to decrease or is delayed (Meyer and Thomsen, 2016;Meyer et al, 2019). In our context, this could suggest that women may refrain from studying, especially in those majors where more men study, and would benefit from less competition for specific apprenticeship occupations, such as in STEM fields.…”
Section: C) Interpretationmentioning
confidence: 84%
“…Another explanation for the gender heterogeneity (and especially the opposite-signed effects in STEM occupations) could be different responses to changes in competitive pressure. As studies on double high school graduation cohorts show, greater competition increases the performance of males relative to females (Ors et al, 2013;Morin, 2015), while the educational attainment of females tends to decrease or is delayed (Meyer and Thomsen, 2016;Meyer et al, 2019). In our context, this could suggest that women may refrain from studying, especially in those majors where more men study, and would benefit from less competition for specific apprenticeship occupations, such as in STEM fields.…”
Section: C) Interpretationmentioning
confidence: 84%
“…First studies examine the G8-reform effects on postsecondary education decisions and university performance, and indeed these studies find only small effects. Meyer et al (2015) and Meyer & Thomsen (2016) find that some students delay the start of university by one year. By the second year after graduation, the effects on the transition to university have almost vanished.…”
Section: Panel C Ofmentioning
confidence: 99%
“…Beyond this, further changes were implemented, which were required to increase instruction time per week, for instance new educational standards and school-specific curricula. Current research on the G8-reform is mixed in that some studies find student achievement to increase in lower secondary school (Huebener et al, 2017), whereas others find zero or negative effects on achievement, negative effects on stress levels and health, and delayed university enrollment of females (e.g., Büttner and Thomsen, 2015;Hübner et al, 2017a;Quis, 2018;Meyer et al, 2019;Marcus et al, 2020). Further studies are needed to investigate potential causes of these reported differences which may result from different samples (e.g., from different states) but also relate to the timeframe examined over which effects might accumulate or dissipate.…”
Section: Introductionmentioning
confidence: 99%